Effectiveness of Bawaslu's Performance in Combating Money Politics in the 2024 Election in Dumbo Raya District - Arsala, Intan Nurain; Wantu, Sastro M; Mahmud, Ramli; Adjie, Zulfikar (Universitas Negeri Gorontalo, 2025)
This study aims to evaluate the effectiveness of the Election Supervisory Agency (Bawaslu) in combating money politics during the 2024 Election in Dumbo Raya District, Gorontalo City. Using a qualitative descriptive method with a phenomenological approach, the research gathered data through interviews, observations, and documentation involving Bawaslu officials, community members, and election stakeholders. The findings reveal that Bawaslu has adopted systematic, participatory, and preventive strategies such as early detection, voter education, and the use of digital platforms for reporting violations. Nevertheless, obstacles including limited personnel, constrained budgets, weak law enforcement, and public tolerance for money politics impede optimal oversight. The study concludes that while Bawaslu's efforts have shown progress, there is a critical need to enhance institutional capacity, reform election laws, integrate digital supervision tools, and promote civic engagement. The study recommends increasing funding, streamlining enforcement mechanisms, and fostering collaboration among various stakeholders to ensure more transparent, fair, and democratic elections.